In Vitro Antioxidant Properties of Methanolic Leaf Extract of Vernonia Amygdalina Del (Nigerian Journal of Physiological Sciences, 2021)
Summary: Various methods employed in evaluating antioxidant activities of various samples gives varying results depending on the specificity of the free radical or oxidant used as a reactant. This study investigated the antioxidant /radical scavenging properties of the methanolic extract of Vernonia amygdalina (MEVA) leaves and studied the relationship between the assay methods. Antioxidant capacity of MEVA was evaluated by measuring the radical scavenging activity (RSA) of MEVA on 1,1-diphenyl-2-picrylhydrazyl radical (DPPH•), nitric oxide (NO) and hydrogen peroxide (HP), hydroxyl radical (OH•) scavenging activity (HRSA), lipid peroxidation inhibition activity (LPIA) against 2,2,-azobis(2-amidinopropane) hydrochloride (AAPH) and Trolox Equivalent Antioxidant Capacity (TEAC) of MEVA against 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS+) radicals as well as the reducing power (RP). Assay methods were subjected to regression analysis and their correlation coefficients calculated. Results were analysed using student‟s t-test and ANOVA. MEVA exhibited highest percentage RSA of 85.8% on HP, followed by DPPH• (29.6%), OH• (26.4%) and least on NO• (21.8%). MEVA inhibited AAPH-induced lipid peroxidation by 30.0% and ABTS-induced radical by 1489% with a marked RP of 0.242±0.01. DPPH correlated excellently with RP (r2 = 0.86), TEAC (r2 = 0.94) and HRSA (r2 = 0.89), the four having good relationship with each other, while LPIA correlated moderately with HP (r2 = 0.48 and NO (r2 = 0.34). MEVA exhibited significant free radical scavenging and antioxidant activities. The assay methods correlates very well and could therefore be employed for investigating and understanding antioxidant properties and scavenging activities of plant materials.
Keywords: Antioxidants; assay methods; correlation coefficient; free radicals; radical scavenging activity; Vernonia amygdalina